A method for floatation separation of positive and negative mixed materials of waste lithium iron phosphate battery

CN117339754BActive Publication Date: 2026-10-09CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311326307.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2026-10-09
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

[0008]本发明要解决的技术问题在于克服现有技术的不足,提供一种废旧磷酸铁锂电池正负极混合材料浮选分离方法,解决废旧磷酸铁锂电池正负极材料分离困难的问题,提高石墨正极材料和磷酸铁锂负极材料分离与回收效率

Benefits of technology

[0032] This invention involves fine grinding of materials to ensure complete dissociation and promote the dissolution of organic films on the electrode material surface. In the coarse flotation stage, a highly efficient emulsifying collector significantly enhances the recovery of hydrophobic graphite materials, greatly reducing the amount of collector required. In the fine flotation stage, multiple rounds of fine flotation ensure the recovery rate of graphite in the final froth product and improve the separation accuracy between graphite and lithium iron phosphate. Deaerated water acts as a deagent and dispersant, reducing lithium iron phosphate particle inclusions in the graphite product while ensuring sufficient collection of hydrophobic graphite materials. In the scavenging stage, multiple scavenging rounds introduce a large number of micro-nano bubbles with pre-assembled flotation agent molecules on their surfaces. These micro-nano bubbles selectively interact with hydrophobic graphite, acting as a secondary collector and enhancing the separation and purification of hydrophobic graphite materials in the coarse flotation sediment. This helps ensure a high grade and high recovery rate of lithium iron phosphate cathode materials in the final flotation sediment product. Overall, the use of water samples with different surface properties instead of traditional flotation reagent solutions or water in the selection and scavenging processes can enhance the flotation effect while reducing overall reagent consumption, achieving a green, efficient, and economical total benefit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117339754B_ABST
    Figure CN117339754B_ABST
Patent Text Reader

Abstract

The application discloses a kind of waste lithium iron phosphate battery positive and negative pole mixed material floatation separation methods, including ore grinding, first roughing, three times of concentration, three times of scavenging and the process flow of all middlings sequential return, and using different surface properties degassing water and micro-nano bubble aqueous solution to replace traditional floatation agent solution or ordinary water in concentration stage and scavenging stage, greatly strengthen the interaction between mineral particles-floatation agent-floatation bubble, can reduce the dosage of floatation agent while improving the separation precision and separation efficiency of graphite negative electrode material and lithium iron phosphate positive electrode material in final product, improve the selectivity and comprehensive recovery rate of positive and negative pole material floatation separation, achieve the sum benefit of green, efficient, economic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of recycling technology for waste lithium iron phosphate batteries, specifically, it relates to a flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries. Background Technology

[0002] The demand for lithium batteries in the modern market is increasing rapidly, resulting in a large number of waste lithium batteries. If these waste lithium batteries are not properly disposed of, the toxic substances contained in the battery electrolyte will damage the soil, pollute water resources, and even threaten human life and health. If the precious metals such as Li, Ni, Co, and Cu in the positive electrode material of the battery are not recycled, it will result in a serious waste of metal resources. Graphite in the negative electrode material of the battery has high density and good conductivity. Recycling and reusing it will help reduce the production cost of new fuel cells.

[0003] Lithium-ion batteries typically use lithium alloys or lithium metal oxides as the positive electrode material (classified by the main components of the positive electrode material into lithium cobalt oxide batteries, lithium manganese oxide batteries, lithium nickel oxide batteries, lithium iron phosphate batteries, nickel-cobalt-aluminum ternary batteries, nickel-cobalt-manganese ternary batteries, etc.), and graphite as the negative electrode material. Among these, lithium iron phosphate batteries have advantages such as high operating voltage, high energy density, good safety performance, low self-discharge rate, and no memory effect. Compared with ternary lithium batteries, spent lithium iron phosphate batteries do not contain precious metals, resulting in lower added value from recycling. Therefore, it is necessary to develop low-cost recycling methods.

[0004] Currently, there are two main methods for recycling spent lithium iron phosphate batteries: pyrometallurgical recycling and wet recycling. Pyrometallurgical recycling primarily involves removing organic binders and other mixed materials adhering to the surface of the electrode material through high-temperature calcination, and then resynthesizing the molten metal material into a new lithium iron phosphate electrode using a high-temperature solid-state method. However, this method requires high-temperature calcination, resulting in high costs and potential environmental pollution. Wet recycling includes organic solvent dissolution, acid-base dissolution, electrolysis, and mineral processing methods (gravity separation, magnetic separation, flotation). After dismantling and crushing, spent lithium iron phosphate batteries become a mixed material mainly composed of graphite and metal oxides. Since graphite anode material is naturally more hydrophobic than metal oxide cathode material, flotation can be considered, allowing the graphite anode material to enter the froth product while the metal oxide cathode material remains in the flotation cell.

[0005] Numerous methods have been reported for separating mixed positive and negative electrode materials of lithium batteries using flotation. The published method (202211012455.6) for separating and recycling waste lithium iron phosphate positive and negative electrode materials involves flotation separation of these materials. During the flotation process, diesel oil is emulsified and used as a collector, enhancing the diesel's collecting capacity and selectivity, reducing the amount of collector required, and simultaneously ensuring more thorough separation of the waste lithium iron phosphate positive and negative electrode materials. However, the tailings lithium iron phosphate positive electrode material obtained by this method only achieves a grade of 99.95% and a combustible gas recovery rate of 97.29% after high-temperature calcination at 850℃ for 4 hours. Furthermore, high-temperature calcination easily damages the lithium iron phosphate structure, resulting in high production costs. The published method (202210985587.0) for improving the flotation separation efficiency of positive and negative electrode materials from waste lithium-ion batteries deviates from the traditional flotation process's addition sequence of "collector-pH adjuster-dispersant-foaming agent," instead using "pH adjuster-dispersant-collector-foaming agent." Pre-adding the collector for pre-adsorption prevents dispersant adsorption on the graphite surface, thus avoiding the inhibitory effect of the dispersant on graphite. However, this method uses diesel and water for ultrasonic emulsification, resulting in a collector dosage of 80–200 g / t in the mixed slurry, leading to relatively high collector consumption. Furthermore, the ultrasonic emulsification process requires complex equipment. On the other hand, in conventional flotation separation of mixed positive and negative electrode materials from waste lithium iron phosphate batteries, low reagent dosage typically results in low recovery rates of combustible gases from the concentrate graphite positive electrode material, while increased reagent dosage reduces reagent selectivity. Multi-stage separation and sequential middlings return process improves the separation accuracy of target minerals and gangue minerals, increasing the final concentrate grade and recovery rate. Repeated scavenging of conventional flotation tailings (sequential return of scavenged concentrate) facilitates the recovery of high-purity tailings products. Micro-nano bubble flotation is one of the most efficient methods for recovering fine particulate materials. In the flotation slurry system, micro-nano bubbles preferentially generate / adsorb on the surface of hydrophobic materials. Through capillary bridging, micro-nano bubbles promote selective aggregation between hydrophobic fine particles, increasing the probability of collision and adhesion between flotation bubbles and particles. Simultaneously, micro-nano bubbles can also act as a "secondary collector" in the flotation system, reducing the consumption of chemical reagents and making it environmentally friendly.

[0006] In summary, existing methods for recycling spent lithium iron phosphate batteries generally suffer from problems such as high reagent consumption, complex equipment, high operating costs, difficulty in improving product recovery rates, and environmental pollution caused by high reagent consumption. Therefore, this paper proposes a green, economical, and efficient flotation separation method for mixed positive and negative electrode materials from spent lithium iron phosphate batteries.

[0007] In view of this, the present invention is proposed. Summary of the Invention

[0008] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries, thereby solving the problem of difficult separation of positive and negative electrode materials of waste lithium iron phosphate batteries and improving the separation and recycling efficiency of graphite positive electrode materials and lithium iron phosphate negative electrode materials.

[0009] To solve the above-mentioned technical problems, the basic concept of the technical solution adopted by the present invention is as follows:

[0010] A flotation separation method for mixed positive and negative electrode materials from waste lithium iron phosphate batteries includes the following steps:

[0011] S1. Add the mixed positive and negative electrode materials of waste lithium iron phosphate batteries to a ball mill for wet grinding, and add a dispersant during the grinding process;

[0012] S2. The slurry obtained in step S1 is transferred to the flotation machine. During the slurry preparation process, inhibitors, collectors and frothers are added in sequence for roughing operation. The froth product (roughing concentrate) is pumped to the flotation machine for cleaning operation, and the sediment (roughing tailings) is pumped to the flotation machine for scavenging operation.

[0013] S3. The rough concentrate obtained in step S2 is continuously refined three times. The water added and the rinsing water during the refining process are deaerated water. No other flotation agents are added during this period. After the three refining processes are completed, the final foam product is the graphite anode material.

[0014] S4. The roughing tailings obtained in step S3 are continuously scavenged three times. The replenishment water and rinsing water during the scavenging process are aqueous solutions containing micro-nano bubbles with surface pre-assembled flotation agents, obtained by treating the flotation agent aqueous solution with a nano-bubble water machine (model XZCP-K-0.75) produced by Yunnan Xiazhichun Environmental Protection Technology Co., Ltd. The aqueous solution is a milky white liquid containing a large number of micro-nano bubbles. The presence of micro-nano bubbles significantly increases the gas-liquid interface area. At the same time, due to the strong stability of nano-bubbles, the transmittance of the obtained micro-milky solution is significantly lower than that of ordinary pure water, and the stability is strong and the decay rate is slow (it can persist for tens of minutes or even several hours). The aqueous solution containing micro-nano bubbles with surface pre-assembled flotation agents is prepared by treating the flotation agent solution with a nano-bubble water machine. No other flotation agents are added during the process. After three scavenging processes, the final flotation sediment is the lithium iron phosphate cathode material.

[0015] S5. The intermediate mineral products obtained in steps S3 and S4 are all processed using a sequential return process to enhance the separation and recovery efficiency.

[0016] Furthermore, in step S1, the slurry mass concentration is 10-40%.

[0017] Furthermore, in step S1, the ball-to-material ratio of the ball mill is 1.5, the grinding time is 3 to 10 minutes, and the content of -0.074 mm particles in the grinding product is 60% to 85%.

[0018] Furthermore, in step S1, the dispersant is one or a combination of sodium carbonate, water glass, and sodium hexametaphosphate, and the amount of dispersant added is 50-300 g / t.

[0019] Furthermore, in step S2, the inhibitor is one or a combination of carboxymethyl cellulose, starch, and calcium oxide, and the amount of inhibitor added is 30-200 g / t.

[0020] Furthermore, in step S2, the emulsifying collector is emulsified diesel oil, and the emulsifier is one or more of Tween 80, Span 80, and NP-10, and the amount of emulsified diesel oil added is 10-100 g / t.

[0021] Furthermore, in step S2, the foaming agent is one or more of butyl ether alcohol, methyl isobutyl methanol, and 2-octanol, and the amount of foaming agent added is 5-40 g / t.

[0022] Furthermore, in step S2, the flotation machine used for roughing is a self-aspirating flotation machine, with a roughing stirring speed of 1600–1900 r / min and a roughing aeration rate of 0.15–0.3 m³ / min. 3 / min, flotation time is 3 to 8 min.

[0023] Furthermore, in step S3, the degassed water is prepared by one of vacuum degassing, ultrasonic degassing, and heating degassing.

[0024] Furthermore, in step S4, the nano bubble water machine is model XZCP-K-0.75, with a self-aspiration rate of 0.2L / min and a circulation processing time of 2–5min.

[0025] Furthermore, in step S4, the foaming agent in the foaming agent solution is one or more of emulsified kerosene, butyl ether alcohol, methyl isobutyl methanol, and 2-octanol, and the concentration of the foaming agent in the solution is 0.1-0.5%.

[0026] Furthermore, in step S3, the aeration rate of the flotation machine used for fine selection is 0.1–0.2 m³. 3 The stirring speed is 1500–2600 r / min, and the flotation time is 3–5 min; the aeration rate of the flotation machine used for scavenging in step S4 is 0.15–0.3 m³ / min. 3 The stirring speed is 1500-2000 r / min, and the flotation time is 5-8 min.

[0027] The method of this invention includes: adding a mixture of positive and negative electrode materials from waste lithium iron phosphate batteries and a dispersant into a ball mill to form a slurry for grinding; transferring the slurry obtained in the grinding stage to a flotation machine, adding an inhibitor, an emulsifying collector, and a frother in sequence, and then performing flotation frothing; pumping the froth product obtained from the roughing stage to the flotation machine for cleaning; pumping the sediment in the slurry after roughing to the flotation machine for scavenging; in the cleaning stage, three cleaning stages are adopted, using degassed water that has undergone pre-degassed treatment as cleaning makeup water and rinsing water, and the final froth product obtained is graphite negative electrode material; in the scavenging stage, three scavenging stages are adopted, using a nano-bubble water machine to cavitate the flotation agent solution to obtain an aqueous solution containing micro-nano bubbles with surface pre-assembled flotation agent as scavenging makeup water and rinsing water, and the final flotation sediment product obtained is lithium iron phosphate positive electrode material; during the cleaning and scavenging processes, the obtained middlings are returned sequentially.

[0028] In the grinding stage, the dismantled waste lithium iron phosphate battery positive and negative electrode mixture and inhibitors are added to a ball mill to prepare a slurry of a certain concentration before grinding. Since both the positive and negative electrode materials (graphite) of lithium batteries are covered with an organic film (mainly composed of polyvinylidene fluoride), their similar surface compositions result in similar hydrophilic and hydrophobic properties, making direct flotation difficult to achieve effective separation. Fine grinding facilitates the complete dissociation of different materials and promotes the swelling or partial dissolution of the organic film on the electrode surface. Adding dispersants during the grinding process effectively disperses materials with different properties, weakening the non-selective aggregation behavior between the positive and negative electrode materials.

[0029] In the roughing stage, the slurry obtained from grinding is transferred to a flotation machine. Depressants, emulsifying collectors, and frothers are added sequentially, followed by flotation to obtain froth products and sediment. The froth products are then pumped back to the flotation machine for further cleaning, while the roughing sediment is pumped back to the flotation machine for scavenging. During flotation, the addition of depressants effectively reduces the hydrophilicity of the positive and negative electrode materials, increases the difference in wettability between them, and promotes their flotation separation. Emulsification improves the dispersion performance of the flotation agent, promotes the selective adsorption of hydrocarbon oils on the relatively more hydrophobic graphite cathode material particles, significantly reduces reagent dosage, and enhances the flotation collection of graphite materials.

[0030] In the refining stage, during the three refining processes, degassed water is used instead of ordinary water as makeup water and rinsing water for the flotation process. The middlings are sequentially returned to form a closed-loop cycle, and the resulting final froth product is the graphite anode material. Multiple refining processes help improve the final concentrate grade. Middlings return can maximize the recovery rate of the final graphite product while ensuring the concentrate grade. Pre-degassing of the water sample significantly reduces the content of naturally occurring dissolved gas nuclei, weakens the nucleation effect of dissolved gases on the surface of hydrophobic particles, significantly reduces the capillary attraction effect between particles, and thus strengthens the deflocculation and secondary selective recombination behavior between particles in the shear field, while weakening the non-selective aggregation behavior between positive and negative electrode materials. Simultaneously, the increased solubility of hydrocarbon oil reagents in the degassed water allows for the selective adsorption of hydrocarbon oils on the surface of highly hydrophobic graphite particles, significantly promoting selective hydrophobic agglomeration between similar graphite particles, thereby significantly improving the separation efficiency and accuracy between positive and negative electrode materials during the refining process.

[0031] In the scavenging stage, a flotation agent solution treated with cavitation was used instead of ordinary water as makeup water and rinsing water during the three scavenging processes. The middlings were returned sequentially, and the final flotation sediment product obtained was the lithium iron phosphate cathode material. Multiple scavenging processes are beneficial to improving the recovery rate of lithium iron phosphate cathode material. The presence of the flotation agent promotes the generation of more and more stable micro- and nano-bubbles during the cavitation process, resulting in a high-concentration micro- and nano-bubble aqueous solution. More importantly, after the flotation agent is pre-assembled on the surface of the micro- and nano-bubbles, it can enhance the bubble loading capacity in the flotation system and selectively interact with the more hydrophobic graphite material, promoting selective agglomeration between graphite particles, acting as a secondary collector, and achieving the effects of green economy and energy saving.

[0032] This invention involves fine grinding of materials to ensure complete dissociation and promote the dissolution of organic films on the electrode material surface. In the coarse flotation stage, a highly efficient emulsifying collector significantly enhances the recovery of hydrophobic graphite materials, greatly reducing the amount of collector required. In the fine flotation stage, multiple rounds of fine flotation ensure the recovery rate of graphite in the final froth product and improve the separation accuracy between graphite and lithium iron phosphate. Deaerated water acts as a deagent and dispersant, reducing lithium iron phosphate particle inclusions in the graphite product while ensuring sufficient collection of hydrophobic graphite materials. In the scavenging stage, multiple scavenging rounds introduce a large number of micro-nano bubbles with pre-assembled flotation agent molecules on their surfaces. These micro-nano bubbles selectively interact with hydrophobic graphite, acting as a secondary collector and enhancing the separation and purification of hydrophobic graphite materials in the coarse flotation sediment. This helps ensure a high grade and high recovery rate of lithium iron phosphate cathode materials in the final flotation sediment product. Overall, the use of water samples with different surface properties instead of traditional flotation reagent solutions or water in the selection and scavenging processes can enhance the flotation effect while reducing overall reagent consumption, achieving a green, efficient, and economical total benefit.

[0033] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art.

[0034] The method of this invention adopts a process flow of one grinding, one roughing, three cleaning, and three scavenging with all middlings sequentially returned. In the cleaning and scavenging stages, deaerated water with different surface properties and micro-nano bubble aqueous solutions are used to replace traditional flotation agent solutions or ordinary water, which greatly enhances the interaction between mineral particles, flotation agent, and flotation bubbles. This can improve the separation accuracy and efficiency of graphite anode material and lithium iron phosphate cathode material in the final product while reducing the amount of flotation agent used, thereby improving the selectivity and overall recovery rate of the flotation separation of cathode and anode materials.

[0035] During the process, fine grinding of materials promotes the swelling or partial dissolution of the organic film on the surface of the electrode material, which is beneficial for the interaction between particles and reagents. In the roughing stage, emulsification of the collector facilitates the uniform dispersion of collector molecules in the slurry, thereby significantly reducing the amount of collector used. In the cleaning stage, deaerated water is used instead of ordinary water as makeup water and rinsing water during multiple cleaning processes, which helps to improve the separation accuracy of positive and negative electrode materials while ensuring a high graphite flotation recovery rate. In the scavenging stage, multiple scavenging processes help to improve the recovery rate of lithium iron phosphate cathode materials. Using an aqueous solution of micro-nano bubbles containing surface pre-assembled flotation agents instead of pure water can significantly enhance the selectivity between hydrophobic graphite particles and flotation bubbles. Moreover, the micro-nano bubbles can also act as a secondary collector, making it environmentally friendly. In summary, compared with existing flotation technologies, the technology presented in this invention can simultaneously and efficiently recover two products: graphite anode materials and lithium iron phosphate cathode materials. It also has the advantages of low flotation agent consumption, low separation cost, and clean and environmentally friendly operation, making it highly valuable for the recycling of waste lithium batteries.

[0036] The specific embodiments of the present invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description

[0037] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments and descriptions of the invention are used to explain the invention, but do not constitute an undue limitation of the invention. Obviously, the drawings described below are merely some embodiments, and those skilled in the art can obtain other drawings based on these drawings without creative effort. In the drawings:

[0038] Figure 1 This is a schematic diagram of the method flow of the present invention;

[0039] Figure 2 This is a flotation flowchart of the present invention;

[0040] Figure 3 It contains actual samples of different types of water and their basic characteristics;

[0041] Figure 4 These are morphological images of diesel emulsion droplets in different types of solutions;

[0042] Figure 5 This is a diagram showing the size distribution of diesel emulsion droplets in different types of solutions;

[0043] Figure 6 This is a diagram showing the aggregation and dispersion of fine black powder in different types of solutions;

[0044] Figure 7 This is a particle size distribution diagram of fine black powder particles in different types of solutions.

[0045] It should be noted that these accompanying drawings and textual descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art by referring to specific embodiments. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below with reference to the accompanying drawings. The following embodiments are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0047] Example 1:

[0048] S1. Place 500g of waste lithium iron phosphate battery positive and negative electrode mixture in a ball mill, add water to 1.5L, add 50g / t dispersant sodium hexametaphosphate, and grind for 5min;

[0049] S2. Transfer the mixed slurry obtained in S1 to the roughing flotation machine, add 50 g / t of inhibitor starch, and adjust the slurry for 3 minutes. Then, add ordinary diesel oil at a dosage of 100 g / t to the roughing flotation machine, adjust the slurry for 3 minutes, and add frother No. 2 oil at a dosage of 50 g / t for flotation. During the flotation process, the slurry volume is 1.5 L, the rotation speed is 1900 r / min, and the aeration rate is 0.2 m³ / min. 3 / min, the flotation scraping time is 5min, the obtained foam product is pumped to the flotation machine for fine selection, and the sediment is pumped to the flotation machine for sweeping selection.

[0050] S3. The roughing froth product obtained in step S2 is subjected to three cleaning processes, using ordinary clean water as flotation replenishment and rinsing water. After adjusting the slurry for 3 minutes, flotation is performed by skimming the froth for 3 minutes, and the middlings are returned sequentially to obtain the final froth product. The flotation machine used for cleaning has a volume of 0.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1600 r / min.

[0051] S4. The roughing sediment obtained in step S2 is subjected to three scavenging processes. Ordinary clean water is added as scavenging replenishment water and rinsing water. After adjusting the slurry for 3 minutes, the middlings are sequentially returned after 3 minutes of flotation to obtain the final flotation sediment product. The scavenging flotation machine has a volume of 1.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1900 r / min.

[0052] S5. Filter and dry the obtained final foam product and final flotation sediment product. Weigh 1.000g of the dried final foam product into a ceramic boat and place it in a muffle furnace. Raise the furnace temperature to 950℃ and keep it at that temperature for 2.5 hours. After cooling the ceramic boat to room temperature, weigh it and calculate the grade and recovery rate of the graphite anode material.

[0053] S6. Take an appropriate amount of the dried final flotation sediment product obtained in S5, determine the content of Li and Fe by fluorescence spectroscopy (XRF), and calculate the recovery rate and grade of lithium iron phosphate cathode material.

[0054] The flotation process revealed that when using ordinary diesel oil and ordinary water, the flotation rate was moderate. This is because conventional hydrocarbon oil collectors have poor dispersibility. Figure 4 A and Figure 5 This results in a longer interaction time between some graphite particles and hydrocarbon oils; meanwhile, the agglomeration effect between black powder particles in ordinary aqueous solutions is generally ( Figure 6 B and Figure 7 This results in some fine graphite particles failing to float effectively and quickly. From a flotation efficiency perspective, the yield of the foam product during the fine scavenging process is generally low. The insoluble hydrocarbon oil collector (diesel) has difficulty fully interacting with the graphite particles, and the conventional agglomeration effect between black powder particles in ordinary water is also generally low. All of these factors contribute to the difficulty in efficiently flotating and recovering some fine graphite particles. Finally, calculations show that the grade and recovery rate of graphite anode material in the final flotation foam product obtained by the flotation separation method for the mixed positive and negative electrode materials of waste lithium iron phosphate batteries described in this embodiment are 95.38% and 96.16%, respectively, while the grade and recovery rate of lithium iron phosphate cathode material in the final flotation sediment product are 94.11% and 93.32%, respectively.

[0055] Example 2:

[0056] S1. Place 500g of waste lithium iron phosphate battery positive and negative electrode mixture in a ball mill, add water to 1.5L, add 50g / t dispersant sodium hexametaphosphate, and grind for 5min;

[0057] S2. Transfer the mixed slurry obtained in S1 to the roughing flotation machine, add 50 g / t of inhibitor starch, and adjust the slurry for 3 minutes. Then, add emulsified diesel oil at a dosage of 100 g / t to the roughing flotation machine, adjust the slurry for 3 minutes, and add frother No. 2 oil at a dosage of 50 g / t for flotation. The roughing slurry volume is 1.5 L, the rotation speed is 1900 r / min, and the aeration rate is 0.2 m³ / min. 3 The flotation time is 5 minutes, and the resulting foam product is pumped to the flotation machine for fine selection. The sediment is pumped to the flotation machine for sweeping.

[0058] S3. The roughing froth product obtained in step S2 is subjected to three cleaning processes, using ordinary clean water as flotation replenishment and rinsing water. After adjusting the slurry for 3 minutes, the middlings are sequentially returned after 3 minutes of flotation to obtain the final froth product. The cleaning process uses a 0.5L flotation machine with an aeration rate of 0.2m³. 3 The stirring speed is 1600 r / min.

[0059] S4. The roughing tailings obtained in step S2 are subjected to three scavenging processes. Ordinary clean water is added as makeup water and rinsing water. After adjusting the slurry for 3 minutes, flotation is performed for 3 minutes. The middlings are returned sequentially to obtain the final flotation sediment product. The flotation machine used for scavenging has a volume of 1.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1900 r / min.

[0060] S5. Filter and dry the obtained final foam product and final flotation sediment product. Weigh 1.000g of the dried final foam product into a ceramic boat and place it in a muffle furnace. Raise the furnace temperature to 950℃ and keep it at that temperature for 2.5 hours. After cooling the ceramic boat to room temperature, weigh it and calculate the grade and recovery rate of the graphite anode material.

[0061] S6. Take an appropriate amount of the dried final tailings obtained in S5, determine the content of Li and Fe by fluorescence spectroscopy (XRF), and calculate the recovery rate and grade of lithium iron phosphate cathode material in the final flotation sediment product.

[0062] The flotation process revealed that, compared to the experiment in Example 1, the flotation rate in Example 2 was improved to some extent when using emulsified diesel and ordinary water. This is because the diesel's dispersibility is enhanced after emulsification. Figure 4 B and Figure 5This leads to a shorter interaction time between the micro-diesel droplets and graphite particles, thereby increasing the flotation speed of the particles. In terms of flotation effect, the yield of finely swept froth products is improved to a certain extent compared with that in Example 1. After the micro-diesel droplets with better dispersibility fully interact with the graphite particles, they are adsorbed on the surface of the graphite particles, strengthening the hydrophobic attraction and capillary bridging between the particles, thereby promoting the selective agglomeration of micro-graphite particles, and thus promoting the flotation recovery of micro-graphite particles. Finally, calculations showed that the grade and recovery rate of graphite anode material in the final flotation foam product obtained by the flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries described in this embodiment were 96.26% and 97.81%, respectively. The grade and recovery rate of lithium iron phosphate cathode material in the final flotation sediment were 94.51% and 94.52%, respectively. Compared with the final flotation foam product without the use of emulsified diesel under the same material conditions, the grade of graphite anode material in the final flotation foam product was increased by 0.88%, and the recovery rate was increased by 1.65%. In the final sediment product, the grade of lithium iron phosphate cathode material was increased by 0.4%, and the recovery rate was increased by 1.2%.

[0063] Example 3:

[0064] S1. Place 500g of waste lithium iron phosphate battery positive and negative electrode mixture in a ball mill, add water to 1.5L, add 50g / t dispersant sodium hexametaphosphate, and grind for 5min;

[0065] S2. Transfer the mixed slurry obtained in S1 to a flotation machine for roughing. Add 50 g / t of inhibitor starch and adjust the slurry for 3 minutes. Then add emulsified diesel oil to the flotation machine at a dosage of 100 g / t and adjust the slurry for 3 minutes. Finally, add frother No. 2 oil at a dosage of 50 g / t for flotation. During the flotation process, the volume of the roughing slurry is 1.5 L, the rotation speed is 1900 r / min, and the aeration rate is 0.2 m³ / min. 3 The flotation time is 5 minutes, and the resulting foam product is pumped to the flotation machine for fine selection. The sediment is pumped to the flotation machine for sweeping.

[0066] S3. The roughing froth product obtained in step S2 is subjected to three refining processes. Deaerated water, prepared by treating water with a Sonic JY-Y215 ultrasonic deaerator for 10 minutes, is used as makeup water and rinsing water for flotation. After slurry conditioning for 3 minutes, flotation is performed for 3 minutes, and the middlings are returned sequentially to obtain the final froth product. The flotation machine used for refining has a volume of 0.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1600 r / min.

[0067] S4. The roughing sediment obtained in step S2 is subjected to three scavenging processes, using clean water as makeup water and rinsing water. After slurry conditioning for 3 minutes, flotation skimming is performed for 3 minutes. The middlings are returned sequentially to obtain the final flotation sediment product. The scavenging flotation machine has a volume of 1.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1900 r / min.

[0068] S5. Filter and dry the obtained final foam product and final flotation sediment product. Weigh 1.000g of the dried final foam product into a ceramic boat and place it in a muffle furnace. Raise the furnace temperature to 950℃ and keep it at that temperature for 2.5 hours. After cooling the ceramic boat to room temperature, weigh it and calculate the grade and recovery rate of the graphite anode material.

[0069] S6. Take an appropriate amount of the dried final flotation sediment product obtained in S5, determine the content of Li and Fe by fluorescence spectroscopy (XRF), and calculate the recovery rate and grade of lithium iron phosphate cathode material.

[0070] The flotation process revealed that when emulsified diesel oil was used as the collector and deaerated water was used instead of ordinary water in the cleaning process, the flotation rate in the cleaning operation of Example 3 did not change significantly compared to the experimental process in Example 2. This is because the addition of deaerated water reduced the gas content of the entire pulp system. Figure 3 A; DO is dissolved oxygen content), which helps to further disperse emulsified diesel ( Figure 4 C and Figure 5 This enhances the interaction between fine diesel droplets and graphite particles, thus strengthening flotation; on the other hand, it weakens the agglomeration effect between particles, reducing the agglomeration size in the system. Figure 6 A and Figure 7 The combined effect of the two factors—reducing the flotation rate and the concentration process—results in a relatively small change in the flotation rate during the refining operation. From a flotation efficiency perspective, due to the inherent hydrophilicity / hydrophobicity difference between the positive and negative electrode materials, the presence of deaerated water further enhances the difference in the homogeneous flocculation effect between them. Simultaneously, it reduces the entrainment effect of the positive electrode material in the graphite foam (reducing the heterogeneous agglomeration effect between the positive and negative electrode materials), ultimately improving the separation accuracy between the positive and negative electrode materials. Finally, calculations show that the final flotation foam product obtained by the flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries described in this embodiment has a graphite negative electrode material grade and recovery rate of 98.58% and 98.01%, respectively. The final flotation sediment product has a lithium iron phosphate positive electrode material grade and recovery rate of 94.83% and 95.03%, respectively. Compared with the test group that did not use deaerated water in the refining stage, the grade of graphite material in the final flotation foam product increased by 2.22%, and the recovery rate increased by 0.2%. The final flotation sediment product has a lithium iron phosphate positive electrode material grade increased by 0.32%, and the recovery rate increased by 0.51%.

[0071] Example 4:

[0072] S1. Place 500g of waste lithium iron phosphate battery positive and negative electrode mixture in a ball mill, add water to 1.5L, add 50g / t dispersant sodium hexametaphosphate, and grind for 5min;

[0073] S2. Transfer the mixed slurry obtained in S1 to a roughing flotation machine, add 50 g / t of inhibitor starch, and adjust the slurry for 3 minutes. Then, add emulsified diesel oil at a dosage of 100 g / t to the flotation machine for roughing, adjust the slurry for 3 minutes, and add frother No. 2 oil at a dosage of 50 g / t for flotation. The roughing slurry volume is 1.5 L, the rotation speed is 1900 r / min, and the aeration rate is 0.2 m³ / min. 3 The flotation time is 5 minutes, and the resulting foam product is pumped to the flotation machine for fine selection. The sediment is pumped to the flotation machine for sweeping.

[0074] S3. The roughing froth product obtained in step S2 is subjected to three refining processes. Deaerated water, prepared by treating water with a Sonic JY-Y215 ultrasonic deaerator for 10 minutes, is used as makeup water and rinsing water for flotation. After slurry conditioning for 3 minutes, flotation is performed for 3 minutes, and the middlings are returned sequentially to obtain the final froth product. The flotation machine used for refining has a volume of 0.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1600 r / min.

[0075] S4. The roughing sediment obtained in step S2 is subjected to three scavenging processes. The flotation agent solution, which has undergone cavitation treatment by a micro-nano bubble water machine for 5 minutes, is used as the scavenging makeup water and rinsing water. After adjusting the slurry for 3 minutes, flotation is performed for 3 minutes. The middlings are returned sequentially to obtain the final flotation sediment product. The scavenging flotation machine has a volume of 1.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1900 r / min.

[0076] S5. Filter and dry the obtained final foam product and final flotation sediment product. Weigh 1.000g of the dried final foam product into a ceramic boat and place it in a muffle furnace. Raise the furnace temperature to 950℃ and keep it at that temperature for 2.5h. After cooling the ceramic boat to room temperature, weigh it and calculate the grade and recovery rate of the graphite anode material.

[0077] S6. Take an appropriate amount of the dried final flotation sediment product obtained in S5, determine the content of Li and Fe by fluorescence spectroscopy (XRF), and calculate the recovery rate and grade of lithium iron phosphate cathode material.

[0078] The flotation process revealed that when emulsified diesel oil was used as the collector in flotation and a solution containing pre-assembled micro / nano bubbles with a flotation agent was used instead of ordinary water in the scavenging process, the flotation rate of the scavenging operation in Example 4 was significantly improved compared to the experimental process in Example 2. This is because the content of dissolved gas nuclei in the solution increased significantly after the cavitation treatment. Figure 3 C) Pre-assembled micro- and nano-bubbles on the surface act as secondary collectors, selectively anchoring themselves on the surface of hydrophobic graphite to enhance the mineralization process between flotation bubbles and graphite particles during flotation. Simultaneously, the micro- and nano-bubbles anchored on the surface of fine-grained graphite can promote selective agglomeration among fine-grained graphite particles through capillary bridging effects. Figure 6 C and Figure 7 This further improves the flotation rate of graphite particles. From the perspective of flotation effect, due to the natural difference in hydrophilicity and hydrophobicity between positive and negative electrode materials, the addition of surface pre-assembled micro-nano bubble solution further enhances the selectivity of reagents and solid particles as well as the flotation mineralization process, promoting the floatation of more graphite particles, thereby improving the recovery rate of scavenging foam products and simultaneously improving the separation accuracy of positive and negative electrode materials. Finally, calculations show that the grade and recovery rate of graphite negative electrode material in the final flotation foam product obtained by the flotation separation method of waste lithium iron phosphate battery positive and negative electrode mixed materials described in this embodiment are 98.69% and 99.12%, respectively, and the grade and recovery rate of lithium iron phosphate positive electrode material in the final flotation sediment product are 96.38% and 97.59%, respectively. Compared with the test group without the introduction of micro-nano bubbles in the scavenging stage (Example 3), the grade of graphite in the final flotation product increased by 0.11%, and the recovery rate increased by 1.11%; the grade of lithium iron phosphate positive electrode material in the final flotation sediment increased by 1.55%, and the recovery rate increased by 2.56%.

[0079] Example 5:

[0080] S1. Place 500g of waste lithium iron phosphate battery positive and negative electrode mixture in a ball mill, add water to 1.5L, add 50g / t dispersant sodium hexametaphosphate, and grind for 5min;

[0081] S2. Transfer the mixed slurry obtained in S1 to a roughing flotation machine, add 50 g / t of calcium oxide inhibitor, and condition the slurry for 3 minutes. Then, add emulsified diesel oil at a dosage of 100 g / t to the flotation machine for roughing, condition the slurry for 3 minutes, and add frother No. 2 oil at a dosage of 50 g / t for flotation. During the flotation process, the volume of the roughing flotation machine is 1.5 L, the rotation speed is 1900 r / min, and the aeration rate is 0.2 m³ / min. 3 The flotation time is 5 minutes, and the resulting foam product is pumped to the flotation machine for fine selection. The sediment is pumped to the flotation machine for sweeping.

[0082] S3. The roughing froth product obtained in step S2 is subjected to three refining processes. Deaerated water, prepared by treating water with a Sonic JY-Y215 ultrasonic deaerator for 10 minutes, is used as makeup water and rinsing water for flotation. After slurry conditioning for 3 minutes, flotation is performed for 3 minutes, and the middlings are returned sequentially to obtain the final froth product. The volume of the refining flotation machine is 0.5L, and the aeration rate is 0.2m³. 3 The stirring speed is 1600 r / min.

[0083] S4. The roughing tailings obtained in step S2 are subjected to three scavenging processes. A flotation agent solution (oil No. 2 and diesel fuel in a 1:1 mass ratio) that has undergone cavitation treatment for 5 minutes using a micro-nano bubble water machine is used as makeup water and rinsing water for scavenging. After slurry conditioning for 3 minutes, flotation is performed for 3 minutes. The middlings are then returned sequentially to obtain the final flotation sediment product. The scavenging flotation machine has a volume of 1.5L and an aeration rate of 0.2m³. 3 The stirring speed is 1900 r / min.

[0084] S5. Filter and dry the obtained final foam product and final flotation sediment product. Weigh 1.000g of the dried final foam product into a ceramic boat and place it in a muffle furnace. Raise the furnace temperature to 950℃ and hold it at that temperature for 2h30min. After cooling the ceramic boat to room temperature, weigh it and calculate the grade and recovery rate of the graphite anode material.

[0085] S6. Take an appropriate amount of the dried final flotation sediment product obtained in S5, determine the content of Li and Fe by fluorescence spectroscopy (XRF), and calculate the recovery rate and grade of lithium iron phosphate cathode material.

[0086] The flotation process revealed that when emulsified diesel oil was used as the collector in the flotation process, degassed water was used instead of ordinary water in the fine flotation process, and a solution containing pre-assembled micro / nano bubbles with flotation agent was used instead of ordinary water in the scavenging process, the flotation rate in the fine scavenging process of Example 5 was improved compared to the experimental processes of Examples 1, 2, 3, and 4. From the perspective of flotation effect, the flotation recovery rate and separation accuracy of both positive and negative electrode materials were improved to varying degrees. Finally, calculations showed that the grade and recovery rate of graphite anode material in the final flotation foam product obtained by the flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries described in this embodiment were 99.04% and 99.35%, respectively. The grade and recovery rate of lithium iron phosphate cathode material in the final flotation sediment product were 96.51% and 98.00%, respectively. Compared with the final flotation foam product using starch as an inhibitor under the same material conditions, the grade was increased by 0.35%, the recovery rate was increased by 0.23%, and the grade of lithium iron phosphate cathode material in the final flotation sediment product was increased by 0.13%, and the recovery rate was increased by 0.41%.

[0087] In summary, compared to Example 1, the flotation separation methods for the mixed positive and negative electrode materials of waste lithium iron phosphate batteries in Examples 2, 3, 4, and 5 can simultaneously improve the graphite recovery rate and grade in the final foam product, as well as the lithium iron phosphate recovery rate and grade in the final flotation sediment product. In Example 2, under the same collector dosage, emulsified diesel has better dispersibility in the slurry and stronger collection ability for graphite positive electrode material particles. In Examples 3 and 4, the introduction of micro-nano bubbles into the selection and scavenging stages further improves the separation efficiency of graphite positive electrode material and lithium iron phosphate negative electrode material. In Example 5, calcium oxide is used as an inhibitor. Calcium oxide also has the function of adjusting the pH of the slurry. The alkaline environment can accelerate the oxidation rate on the surface of lithium iron phosphate positive electrode material particles, hinder the adsorption of the collector on the surface of the positive electrode material particles, thus inhibiting its flotation and improving the graphite grade in the final foam product.

[0088] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-described technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries, characterized in that, Includes the following steps: S1. Add the mixed positive and negative electrode materials of waste lithium iron phosphate batteries into a ball mill for wet grinding, and add a dispersant during the grinding process; S2. The slurry obtained in step S1 is transferred to the flotation machine. During the slurry preparation process, inhibitors, collectors and frothers are added in sequence for roughing. The roughing concentrate is pumped to the flotation machine for cleaning. The roughing tailings are pumped to the flotation machine for scavenging. S3. The rough concentrate obtained in step S2 is continuously refined three times. During the refining process, the water added and the rinsing water are pre-degassed water. After the three refining processes are completed, the final foam product is the graphite concentrate. The degassed water is prepared by vacuum degassing, ultrasonic degassing or heating degassing. S4. The rough tailings obtained in step S2 are continuously scavenged three times. During the scavenging process, the water added and the rinsing water are aqueous solutions containing micro-nano bubbles with surface pre-assembled flotation agents obtained by treating the flotation agent aqueous solution with a nano bubble water machine. After the three scavengings are completed, the final flotation sediment is lithium iron phosphate concentrate. In the selection and scavenging stages, deaerated water and micro / nano bubble aqueous solutions with different surface properties are used to replace traditional flotation agent solutions or ordinary water, which strengthens the interaction between mineral particles, flotation agents, and flotation bubbles, reduces the amount of flotation agent used, and improves the separation accuracy and efficiency of positive and negative electrode materials. S5. The intermediate mineral products obtained in steps S3 and S4 are all processed using a sequential return process.

2. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The mass concentration of the slurry obtained in step S1 is 10-40%.

3. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: In step S1, the ball-to-material ratio in the wet grinding of the ball mill is 1.5, the grinding time is 3 to 10 minutes, and the content of -0.074 mm particles in the grinding product is 60% to 85%.

4. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The dispersant mentioned in step S1 is one or a combination of sodium carbonate, water glass, and sodium hexametaphosphate, and the amount of dispersant added is 50-300 g / t.

5. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The inhibitor mentioned in step S2 is one or a combination of carboxymethyl cellulose, starch, and calcium oxide, and the amount of inhibitor added is 30-200 g / t. The collector is emulsified diesel oil, and the amount of emulsified diesel oil added is 10-100 g / t; The foaming agent is one or more of butyl ether alcohol, methyl isobutyl methanol, and 2-octanol, and the amount of foaming agent added is 5-40 g / t.

6. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: In step S2, the flotation machine used for roughing operates at a stirring speed of 1600–1900 r / min and an aeration rate of 0.15–0.3 m³ / min. 3 / min, flotation time is 3 to 8 min.

7. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The nano bubble water machine described in step S4 has a self-aspiration rate of 0.2L / min and a circulation processing time of 2~5min.

8. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: The flotation agent mentioned in step S4 is one or more of emulsified kerosene, butyl ether alcohol, methyl isobutyl methanol, and 2-octanol, and the mass concentration of the flotation agent is 0.1-0.5%.

9. The flotation separation method for mixed positive and negative electrode materials of waste lithium iron phosphate batteries according to claim 1, characterized in that: In step S3, the aeration rate of the flotation machine used for fine separation is 0.1–0.2 m³. 3 The stirring speed is 1500–2600 r / min, and the flotation time is 3–5 min; the aeration rate of the flotation machine used for scavenging in step S4 is 0.15–0.3 m³ / min. 3 The stirring speed is 1500-2000 r / min, and the flotation time is 5-8 min.

Citation Information

Patent Citations

  • A method for improving the flotation separation efficiency of positive and negative electrode materials of waste lithium batteries

    CN115213023B

  • Separation and recovery method of waste lithium iron phosphate positive and negative electrode materials

    CN115672560A

  • Efficient separation and recovery method for valuable substances in waste lithium battery electrode powder

    CN115863822A

  • Device for strengthening flotation separation of anode and cathode materials in waste lithium cobalt oxide battery

    CN219309020U